Prognostic implications of serum ferritin levels in non-anemic women with stage 3 chronic kidney disease - Liao, Min-Tser; Lu, Chien-Lin; Hou, Yi-Chou; Wang, Joshua; Tsai, Kuo-Wang; Shih, Li-Jane; Wu, Chia-Chao; Wang, Yi-Chun; Lu, Kuo-Cheng (Frontiers in Nutrition, 2025)
IntroductionChronic kidney disease (CKD) is often accompanied by iron deficiency and persistent inflammation, both of which complicate the evaluation of iron metabolism and its clinical relevance. Although serum ferritin is commonly used to assess iron status in anemic CKD patients, data on its prognostic value in non-anemic, iron-deficient individuals remain limited and inconclusive.MethodsThis retrospective cohort study utilized the TriNetX database to evaluate 5-year clinical outcomes in adult women with stage 3 chronic kidney disease (CKD), normal hemoglobin levels (≥12 g/dL), normal mean corpuscular volume (MCV, 80–100 fL), and varying serum ferritin concentrations. Patients were stratified into two groups based on ferritin levels: <100 ng/ml (low ferritin) and 100–700 ng/ml (adequate ferritin). Primary outcomes included all-cause mortality, major adverse cardiovascular events (MACE), acute kidney injury (AKI), pneumonia, fractures, and progression to advanced CKD (estimated glomerular filtration rate < 30 ml/min/1.73 m2).ResultsA total of 66,768 eligible non-anemic women with stage 3 CKD, low serum ferritin levels, and normal MCV were identified. Propensity score matching (1,1) based on demographic variables was performed prior to comparing outcomes between low ferritin (n = 52,295) and adequate ferritin (n = 52,295) cohorts. Over 5 years, low ferritin—relative to adequate ferritin—was associated with significantly lower hazards of AKI, CKD progression, and pneumonia (HRs 0.909, 0.953, and 0.956; log-rank p < 0.05, <0.01, and <0.005, respectively). By contrast, low ferritin—relative to adequate ferritin—was associated with a significantly higher fracture hazard (HR 1.125; log-rank p < 0.05). No significant differences were observed in all-cause mortality or MACE. Low ferritin was associated with lower all-cause mortality at years 1–3 (ORs: 0.739, p < 0.001; 0.842, p < 0.05; 0.895, p = 0.038) and to a lower cumulative incidence of CKD progression at years 2–5 (ORs: 0.888 at year 2, 0.898 at year 3, 0.907 at year 4, 0.914 at year 5; all p < 0.05). Subgroup analysis revealed that low ferritin levels were especially protective against AKI and pneumonia in patients with elevated CRP (>10 mg/L), postmenopausal women, and those aged 18–64. The association of low ferritin levels with enhanced renal function preservation was more pronounced in postmenopausal women, individuals with vitamin D ≥ 30 ng/ml, and patients with diabetes. Conversely, adequate ferritin was associated witha lower fracture risk in older adults (>65 years) and those with vitamin D < 20 ng/ml.ConclusionThis study of non-anemic female patients with stage 3 CKD found that adequate ferritin levels correlated with a heightened risk of AKI, renal disease progression, and pneumonia. In contrast, low ferritin levels were associated with a higher fracture risk but a lower likelihood of renal function deterioration.